Feasibility and Acceptability of a Telephone-Based Intervention for Hispanic Children to Promote Treatment Adherence After Traumatic Brain Injury: A Pilot Study. Issue 4 (22nd July 2021) - Jimenez, Nathalia; Fuentes, Molly; Virtue, Alyssa; Alonso-Gonzalez, Laura; Lopez, Edgar; Zhou, Chuan; Crawley, Deborah; Apkon, Susan; Johnston, Brian; Rivara, Frederick
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To assess the feasibility and acceptability of a telephone-based education and navigation program for Hispanic parents of children hospitalized with traumatic brain injury (TBI). Setting: Level I trauma hospital and pediatric inpatient rehabilitation unit in the Northwestern United States. Participants: Fourteen Hispanic parent-child dyads. Parents were 85% female, with a mean age of 35 years. Children were 58% male, with a mean age of 9.7 years, and had been hospitalized for complicated mild/moderate ( n = 5) or severe ( n = 9) TBI. Design: Pilot prospective cohort design. Main Measures: Feasibility measures include recruitment, retention, and intervention adherence rates. Acceptability of intervention was measured by parents' use of educational materials and satisfaction with navigation program. We also evaluated study processes, including completion of baseline, 3, 6, and 12 months functional assessments of the child; assessment of parental health literacy and self-efficacy; and adherence to follow-up rehabilitation appointments. Results: Eighty-two percent of approached potential participants were recruited into the study. One hundred percent of participants completed the intervention, and 85% had 1-year follow-up. Intervention acceptability was high: 90% reported satisfaction with navigator, and 92% used the educational manual. Assessments demonstrated significant improvement in parents' TBI caregiving and community self-efficacy; 92% attendance to follow-up rehabilitation appointments; and improvement in the child's functional measures, except communication skills. Conclusions: Findings support feasibility and acceptability of a culturally relevant program to facilitate transitions of care for Hispanic children with TBI. A future randomized trial is warranted to determine the efficacy of the intervention on long-term treatment adherence and the child's post-TBI function.